Les mobiles de la mobilité : Exhibition for the Erasmus Prize Award Ceremony 4 december 1994. - Théâtre du Résidence Palace, Bruxelles (Brussel : Commission of the European Communities, 1994)
Bouvier, Mathias ; Brandt, Pierre-Alain ; Pijuan, Yolanda Cebria ; Da Silva, Pascal ; Eastwood, Steven John ; Ferretti, Mario ; Fielding, Nick ; Fitzgerald, Peter ; Mc Carthy, Conor ; Milson, Anthony ; Morison, Lucy Ateca ; Roman, Ilse ; Steen, Tine ; Zwakman, Edwin
An exhibition of work by Fine Art students who have recently participated in a ERASMUS Student Mobility Programme: ICP-UK-1241
Les mobiles de la mobilité : Exhibition for the Erasmus Prize Award Ceremony, Théâtre du Résidence Palace, Brussel, 4 december 1994
boek